In-silico and in-vitro hybrid approach to identify glucagon-like peptide-1 receptor agonists from anti-diabetic natural products. Issue 10 (19th May 2023) - Chatterjee, Debanjan; Vhora, Nazmina; Goswami, Ashutosh; Hiray, Aishwarya; Jain, Alok; Kate, Abhijeet S.
Abstract: Natural products have contributed immensely towards the treatment of various diseases including diabetes. Here, a database of small molecules from nature possessing antidiabetic properties was analysed and shortlisted according to their structural diversity. Later, those structures were screened by in-silico docking studies to understand their affinity towards glucagon-like peptide-1 (GLP-1) receptor. The selected molecules were isolated and investigated further by integrated in-vitro and in-silico approaches. Alpha-mangostin was found to be suitable due to its excellent docking score and isolation yield. A pancreatic beta cell line was used to test the activity of alpha-mangostin and observed a 3-fold increase in insulin secretion compared to 15 mM glucose control. Further, in-silico molecular dynamics simulations studies have validated its target by showing conformational changes at the functionally active part of the GLP-1 receptor. This screening strategy can be applied to identify pertinent natural products rapidly for various therapeutic targets. Graphical Abstract: UF0001